Anuros del norte de los andes: patrones de riqueza de especies y estado de conservación - Armesto, Luis Orlando; Señaris, Josefa Celsa (Papéis Avulsos de Zoologia, 2017)
Knowledge of Andean anurans is constantly increasing; for this reason, it needs an update. We reviewed scientific literature and museum records to determine the species richness of anurans in the northern Andes and their conservation status based on the IUCN categories. The northern Andes harbor 740 species of anurans, belonging to 13 families and 63 genera. The family with the highest species number was Craugastoridae (334 spp.), followed by Bufonidae (92 spp.), and Centrolenidae (81 spp.). The Cordillera Central of Colombia harbors the highest species richness (199 spp.), while the Cordillera de la Costa Oriental de Venezuela contains the lowest species number (17 spp.). Most species (74%) is endemic to the northern Andes, but no family is endemic to the northern Andes. About 50% species is threatened and 20% is included in the category of deficient data. The species richness patterns in northern Andes might be caused, among other reasons, by historical factors, but also result of sampling lack in some areas.